A method for preparing carbon fiber-reinforced thermoplastic composites by okra-kiwi stem green suspension
Patent Information
- Application Number
- CN202611037110.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-13
- Publication Date
- 2026-10-30
AI Technical Summary
[0005]针对现有碳纤维增强热塑性复合材料制备中悬浮液分散剂成本高、需额外引入化学试剂、残留污染界面且难以彻底退出,叠层预浸料工艺层间剪切强度受限,孔隙率偏高以及纤维用量大等问题,本发明提供一种低成本、绿色环保、超高层间性能、超低孔隙率且可在较低碳纤维含量下实现高强度的复合材料制备方案
[0023]本发明中全生物质绿色悬浮液发挥三重作用:
Smart Images

Figure CN123001268A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of carbon fiber reinforced thermoplastic composite (CFRTP) preparation technology, specifically involving a process for preparing carbon fiber reinforced thermoplastic composites using a wet felting process with a whole biomass green suspension as the dispersion medium and a two-stage pre-compression molding process. Background Technology
[0002] Carbon fiber reinforced thermoplastic composites use carbon fiber as the reinforcement and thermoplastic resin as the matrix. They combine the characteristics of lightweight, high specific strength, high specific modulus, corrosion resistance and recyclability, and are widely used in aerospace, rail transportation, automobiles and high-end industrial equipment. Commonly used thermoplastic matrices include polyetheretherketone (PEEK), polyamide (PA), polyphenylene sulfide (PPS), polyetherimide (PEI) and polypropylene (PP).
[0003] The preparation of this type of composite material requires simultaneously addressing issues such as carbon fiber dispersion and orientation, interfacial bonding between the fiber and the matrix, and the sufficient impregnation of the fiber bundle by a high-viscosity thermoplastic melt. Currently, high-performance parts are mainly produced by layering continuous fiber prepregs, stacking them, and then hot-pressing them, resulting in a laminated structure. There are also attempts to disperse carbon fibers in a liquid phase to form fiber mat preforms before impregnation molding, and the interfacial bonding between the fiber and the matrix is commonly improved through surface oxidation, coating with coupling agents, or sizing. However, due to limitations imposed by the dispersion medium, molding method, and matrix impregnation capacity, these approaches still have significant limitations in terms of preparation cost, environmental friendliness, interlayer performance, and porosity control.
[0004] Specifically, existing technologies have the following main shortcomings: First, the dispersants used in liquid phase dispersion are mostly synthetic or semi-synthetic polymers such as carbomer, polyethylene glycol (PEG), and hydroxypropyl methylcellulose (HPMC), and often require the addition of chemical pH adjusters. The raw materials are expensive and lack stability, making it difficult to balance greenness and low cost. Second, these dispersants do not decompose completely thermally and tend to remain at the fiber-matrix interface after hot pressing, contaminating the interface and making it difficult to completely remove from the dense part, thus becoming a source of internal defects. Third, laminated prepreg parts have weak interlayer interfaces rich in resin, which are prone to delamination failure, and the interlaminar shear strength (ILSS) is generally lower than 100 MPa. Fourth, PEEK and other melts have high viscosity, making it difficult to fully impregnate with conventional hot pressing, resulting in high porosity (about 3-8%), which reduces tensile, flexural and other mechanical properties. Fifth, to achieve the mechanical properties, a high carbon fiber content of 60-70 wt% is often required, further increasing costs and manufacturing difficulty. The aforementioned problems make it difficult to meet the requirements of low cost, greenness, high performance and large-scale application of high-end structural components. Summary of the Invention
[0005] To address the problems in the preparation of existing carbon fiber reinforced thermoplastic composites, such as high cost of suspension dispersants, the need to introduce additional chemical reagents, residual pollution at the interface that is difficult to completely remove, limited interlayer shear strength in laminated prepreg processes, high porosity, and large fiber usage, this invention provides a low-cost, environmentally friendly composite material preparation scheme with ultra-high interlayer performance, ultra-low porosity, and the ability to achieve high strength with relatively low carbon fiber content.
[0006] The technical solution adopted in this invention is as follows:
[0007] A method for preparing carbon fiber reinforced thermoplastic composite material using okra-kiwi vine stem green suspension method, characterized by comprising the following steps:
[0008] (1) Short carbon fiber filaments are desizing and surface modified to obtain modified carbon fiber, so as to improve the interfacial bonding performance between carbon fiber filaments and thermoplastic matrix.
[0009] (2) Using okra pod polysaccharide (OPP) and kiwi vine stem exudate polysaccharide (KVSEP) in a mass ratio of 2:1 to 5:1 and dissolved in water to form a whole biomass green suspension as the dispersion medium, the total mass concentration of the suspension is 0.1 to 0.4 wt%; modified carbon fiber and thermoplastic fiber are added to the suspension in a weight ratio of 1:9 to 1:1 and wet-mixed evenly; a whole biomass green suspension composed only of OPP, KVSEP and water is obtained. When the suspension is left to stand, it inhibits fiber sedimentation. When it is dispersed by high shear or ultrasonic dispersion, it facilitates uniform fiber dispersion. The acidic carboxylic acid group of OPP is negatively charged after ionization, forming electrostatic steric hindrance on the surface of fibers and particles. KVSEP forms a physical adsorption protective layer on the carbon fiber-water interface and the surface of thermoplastic fibers. The viscosity, viscoplastic rheological behavior, surface charge and pH of the suspension are controlled by the concentration of OPP and KVSEP and their mass ratio.
[0010] The OPP used in this invention is derived from okra food processing waste pods. It is an acidic polysaccharide composed of galacturonic acid, rhamnose, galactose and arabinose, with a weight-average molecular weight (Mw) of 80-300 kDa. KVSEP is derived from the exudate from the cut ends of waste kiwi vines after pruning. It is an arabinogalactan with galactose as its backbone, with a weight-average molecular weight (Mw) of 150-600 kDa.
[0011] (3) Filter the mixture obtained in step (2) and dry it until the residual moisture is ≤0.08wt% to obtain carbon fiber / thermoplastic fiber felt. Filtering and drying remove the aqueous phase from the suspension.
[0012] (4) The felt material described in step (3) is hot-pressed using a two-stage pre-pressing-molding process: First, in the pre-pressing stage, the temperature is raised to the thermal decomposition temperature range of OPP and KVSEP under a pressure of 0.2~1MPa, that is, 245~315℃ (KVSEP about 245~295℃, OPP about 270~315℃) and kept at this temperature for 10~20min. At this stage, the felt material has not yet become dense and remains loose and breathable, so that the residual OPP and KVSEP in the felt material can be kept at a low temperature. The polysaccharide is completely pyrolyzed into CO2 and H2O and released through the pore channels of the fiber felt. Then, in the molding section, the temperature is raised to above the melting or softening temperature of the thermoplastic fiber but below the thermal decomposition temperature to melt it. The pressure is then increased to 1~20MPa and held for 10~40min to allow the melt of the thermoplastic fiber to fully infiltrate the carbon fiber and solidify it. The internal air bubbles are released by utilizing the residual pore channels in the felt. Finally, the temperature is gradually reduced, the pressure is held, and the material is demolded to obtain a carbon fiber reinforced thermoplastic composite board.
[0013] Preferably, the surface modification treatment of carbon fiber in step (1) includes one of the following: sizing coating, surface oxidation, chemical grafting, and plasma treatment, or a combination of different modification methods; the sizing coating uses a thermoplastic sizing agent that is homologous to or compatible with the selected thermoplastic matrix and resistant to the corresponding processing temperature (e.g., using aminated PEEK or polyetherimide sizing agents for PEEK matrix, and waterborne polyurethane or waterborne polyamide sizing agents for PA matrix), with a sizing agent concentration of 0.5~2wt% and a treatment time of 2~10min. This improves the interfacial compatibility and wettability between carbon fiber and thermoplastic matrix, extends the material's service life, and reduces costs.
[0014] Preferably, the carbon fiber in step (1) is short-cut carbon fiber with a length of 30~100mm, a single filament diameter of 5~10μm, a tensile strength ≥3000MPa, and an elastic modulus ≥230GPa.
[0015] Preferably, the viscosity, viscoplastic rheological behavior, surface charge, and pH of the whole biomass green suspension described in step (2) are controlled by adjusting the concentration and mass ratio of OPP and KVSEP. This suspension does not rely on any added chemical dispersants or chemical pH adjusters. When the proportion of OPP increases, the carboxylate density of the system increases, the negative charge is enhanced, the electrostatic steric hindrance effect is increased, and the pH tends to be acidic. When the proportion of KVSEP increases, the amphiphilic steric hindrance protection is enhanced, and the pH tends to be neutral. Thus, by simply changing the total concentration and mass ratio of OPP and KVSEP, the dispersion performance and pH of the suspension can be adjusted synchronously and continuously within the working range of weakly acidic to neutral, completely eliminating the need for chemical dispersants such as Triton and chemical pH adjusters such as triethanolamine required in traditional systems, making the suspension a true whole biomass system.
[0016] Preferably, when OPP and KVSEP are mixed in a mass ratio of 3:1 to 4:1 to form a suspension, the thixotropic index (TI) is 3.5 to 7.0. By finely adjusting the ratio of the two within this range, the carbon fiber filaments and thermoplastic fibers can be uniformly dispersed in the suspension without sedimentation, and the pH of the system can be stabilized within a suitable working range without the need to add any chemical pH adjusters.
[0017] Preferably, the thermoplastic fiber in step (2) is a thermoplastic short fiber made by cutting continuous filaments obtained by melt spinning of thermoplastic resin. The diameter of the single filament is 10~50μm and the length is 50~100mm. This length range takes into account the dispersibility of short fibers and the reinforcement efficiency of longer fibers. Compared with shorter fibers, it can form a more complete three-dimensional overlap and stress transfer network in the felt material, and it can bridge through in the thickness direction, which significantly improves the tensile, bending and interlaminar shear strength of the composite material. Compared with continuous fibers, it can be adapted to uniform dispersion by suspension method and complex irregular part molding, and has good mechanical isotropy.
[0018] The thermoplastic resin is one or a combination of two or more of polyetheretherketone (PEEK), polyamide (PA), polyphenylene sulfide (PPS), polyetherimide (PEI), and polypropylene (PP). The thermoplastic fibers intertwine and overlap with carbon fiber filaments in the suspension, forming a three-dimensional network skeleton of interlocking fibers. Compared to resin powder, thermoplastic fibers can intertwine and overlap with carbon fiber filaments during suspension dispersion and felting processes, forming a three-dimensional network skeleton of interlocking fibers. This significantly improves the structural stability of the felt material, prevents resin from migrating and losing in particulate form during felting and hot pressing, resulting in a more uniform resin distribution in the felt material, lower porosity after impregnation, and more stable interlayer and overall mechanical properties.
[0019] Preferably, the hot pressing parameters for different thermoplastic matrices in step (4) are as follows: PEEK matrix hot pressing temperature 360~400℃, pressure 5~20MPa; PA or PP matrix hot pressing temperature 180~300℃, pressure 1~5MPa; PEI or PPS matrix hot pressing temperature is adjusted accordingly between PEEK and PA. For semi-crystalline thermoplastic resins such as PEEK, PA, and PPS, further heat treatment (annealing) can be performed after hot pressing to control the crystallinity of the matrix, eliminate internal stress, and further improve the mechanical properties and dimensional stability of the composite material.
[0020] Preferably, the hot pressing device is a device capable of precisely applying stable pressure and controllable temperature to carbon fiber felt, such as a flat vulcanizing machine, a continuous hot pressing molding machine, or a multi-layer hot pressing unit. Preferably, the present invention uses a flat vulcanizing machine as the hot pressing molding device for carbon fiber felt.
[0021] The present invention also provides a carbon fiber reinforced thermoplastic composite material prepared by the okra-kiwi vine stem green suspension method using any one of the methods described above, characterized in that the carbon fiber reinforced thermoplastic composite material plate is an integral homogeneous structure formed by three-dimensional random entanglement of carbon fibers and thermoplastic fibers, without resin-rich interlayer weak surfaces.
[0022] The beneficial effects of this invention are:
[0023] In this invention, the all-biomass green suspension plays a triple role:
[0024] First, as a dispersion medium, relying on the synergistic viscoplastic rheological behavior of OPP and KVSEP, the dispersion performance and pH can be controlled by simply changing the concentration ratio of the two, so that the carbon fiber filaments and thermoplastic fibers are uniformly dispersed, do not agglomerate, and do not settle, effectively solving the problem of easy agglomeration and uneven dispersion of carbon fibers, without the need to introduce any chemical dispersants and chemical pH adjusters throughout the process.
[0025] Secondly, its raw materials are derived from agricultural waste, which is extremely low in cost and eliminates the need for chemical additives, thus significantly reducing the cost of reinforcing agent preparation.
[0026] Third, and this is the key to the invention, the two polysaccharides can be completely pyrolyzed into CO2 and H2O in the pre-compression molding stage of the two-stage pre-compression-molding process, i.e., before the densification of the composite material, within their thermal decomposition temperature range (KVSEP approximately 245~295℃, OPP approximately 270~315℃). This allows for the complete removal of the suspension without residue, thanks to the loose and breathable nature of the felt material and the free escape of pyrolysis gases through the pore channels of the fiber felt. It is precisely the synergistic effect of the green suspension (which can be completely pyrolyzed and has extremely low inorganic ash content) and the two-stage pre-compression-molding process (first, the pre-compression molding stage involves venting and removal, followed by the molding stage involving pressurization, impregnation, and consolidation) that enables the suspension to "completely exit," fundamentally avoiding the problem of residual dispersants contaminating the interface and being difficult to remove from the composite material, while simultaneously bringing about reduced porosity, cleaner interfaces, and increased strength.
[0027] This invention applies a preset pressure and temperature to carbon fiber / thermoplastic fiber felt using a specific hot-pressing device. First, in the pre-pressing stage, residual polysaccharides in the felt are completely pyrolyzed under low pressure. Gases and volatiles generated inside are then expelled through the porous channels of the fiber felt, and the suspension is completely removed without residue. Next, in the molding stage, the thermoplastic fibers melt and flow, fully wetting the surface of the carbon fibers. After cooling and solidification, a dense composite material sheet is formed. Because the thermoplastic fibers and carbon fibers form an interlocking entanglement network in the felt, after melting, they can directly wet surrounding fibers, avoiding long-distance migration, thus ensuring uniform impregnation and a porosity of less than 0.5%.
[0028] In this invention, the wet-process integrated felting of suspension enables short-cut carbon fibers and thermoplastic fibers to be randomly entangled in three dimensions, forming an overall homogeneous structure without interlayer weak surfaces. On the one hand, this eliminates the resin-rich interlayer weak surfaces of traditional laminated prepreg processes, significantly increasing the interlayer shear strength (ILSS) to over 200 MPa. On the other hand, it allows the molten resin to wet the surrounding fibers nearby, avoiding long-distance migration. Combined with the early withdrawal of the suspension and its excellent dispersion uniformity, the porosity of the composite material is reduced to below 0.5%, and the mechanical properties are stable. Moreover, the above-mentioned high performance can be achieved with a relatively low carbon fiber content of only 10~50 wt%.
[0029] This invention achieves the comprehensive advantages of carbon fiber reinforced thermoplastic composites, including low cost, environmental friendliness, ultra-high interlayer shear strength, ultra-low porosity, high strength, low fiber content, and ease of industrialization. The raw materials are derived from agricultural waste such as okra processing waste and discarded kiwi vine stems, resulting in low costs. Furthermore, it eliminates the need for additional chemical dispersants and pH adjusters, significantly reducing the cost of reinforcement preparation. It utilizes a green, all-biomass suspension composed of only two biopolysaccharides, with dispersion and pH controlled by concentration ratios to further reduce reinforcement preparation costs. The synergistic effect of this suspension with a two-stage pre-compression molding process ensures complete suspension removal and residue-free green preparation. Moreover, the integrated wet-process felting of the suspension creates a homogeneous structure without interlayer weaknesses, guaranteeing ultra-high interlayer shear strength and ultra-low porosity, while achieving high strength with even lower carbon fiber content. This fills the gap in existing technologies where performance, cost, and environmental protection are difficult to balance, and interlayer performance in laminated structures is limited. It is suitable for the large-scale application needs of composite materials in aerospace, rail transportation, automotive, high-end industry, and medical device fields. Attached Figure Description
[0030] Figure 1 This is a process flow diagram of the preparation process of carbon fiber reinforced thermoplastic composite material using the okra-kiwi vine stem green suspension method described in this invention. Detailed Implementation
[0031] The invention is further illustrated below with specific embodiments, but is not limited to these embodiments. In all embodiments, the thermoplastic fibers are obtained by melt spinning and chopped short fibers from the corresponding thermoplastic resin (single filament diameter approximately 20 μm), and the carbon fibers are Toray T700 grade chopped carbon fibers. OPP and KVSEP are extracted from agricultural waste according to the following method. In each embodiment, the carbon fiber content is controlled in a lower range of 10-30 wt%, far lower than the 60-70 wt% commonly used in traditional processes, to verify that the invention can achieve high strength with extremely low carbon fiber content.
[0032] Example 1 (PEEK matrix, 50mm carbon fiber, carbon fiber content 25wt%)
[0033] A1, carbon fiber filaments are desizing in a 500℃ high-temperature furnace for 1 hour.
[0034] A2. The desized carbon fiber was cut to 50mm, sized and modified in a 1wt% ammoniated PEEK sizing agent aqueous dispersion for 5min, and then dried to obtain modified carbon fiber.
[0035] A3. Weigh 0.45g of okra pod polysaccharide (OPP) and 0.12g of kiwi vine stem exudate polysaccharide (KVSEP) (mass ratio approximately 3.75:1), dissolve in 15L of deionized water, stir at 500rpm and 45℃ for 40min until fully dissolved, to obtain a whole biomass green suspension with strong viscous plasticity and pH that is naturally determined by the OPP / KVSEP ratio; no chemical dispersants or chemical pH adjusters are added throughout the process.
[0036] A4. Add 12g of modified carbon fiber to the green suspension, pre-disperse by combing stirring for 5min, and then start ultrasonic dispersion. The carbon fiber is evenly dispersed by the steric hindrance and viscoplasticity of the OPP / KVSEP system itself, without the need to add any dispersant. Then add 36g of PEEK fiber (25wt% carbon fiber content, CF:PEEK=1:3) and wet mix for 10min, then filter.
[0037] A5. After filtering, the felt material is dried by hot air circulation at 130℃ for 6 hours to completely remove the aqueous phase, thus obtaining carbon fiber / PEEK fiber felt material.
[0038] A6. Place the carbon fiber felt in a 200×150mm mold, place it on a flat vulcanizing machine, and hot-press it according to a two-stage pre-compression molding process: ① Pre-compression molding stage—heat to 300℃ at 5℃ / min, maintain low pressure at 0.3MPa for 15min, so that the residual OPP / KVSEP polysaccharide is completely pyrolyzed into CO2 and H2O in a breathable state within this thermal decomposition temperature range, and is discharged and escaped through the pore channels of the fiber felt, the suspension is completely removed, and there is no residue, achieving low bubble and low temperature. Porosity; ② Molding stage - continue heating to 380℃ at 5℃ / min, pre-press at 0.5MPa to melt PEEK fibers and hold for 5min, then pressurize to 16MPa and hold for 30min, and use the residual pore channels in the felt to release internal air bubbles, achieving dense structure and high crystallinity; finally, gradient cooling and pressure holding, cooling to 300℃ at 3℃ / min, cooling to 200℃ at 7℃ / min, cooling to room temperature at 15℃ / min, maintaining 10MPa pressure throughout, and demolding.
[0039] A7. The resulting sheet was annealed at 250°C for 1 hour and then slowly cooled.
[0040] Example 2 (PA6 matrix, 50mm carbon fiber, carbon fiber content 15wt%)
[0041] A1, carbon fiber filaments are desizing in a 500℃ high-temperature furnace for 1 hour.
[0042] A2. The desized carbon fiber was cut to 50mm, sized and modified in a 1wt% aqueous dispersion of water-based polyurethane sizing agent for 5min, and then dried to obtain modified carbon fiber.
[0043] A3. Weigh 0.45g of okra pod polysaccharide (OPP) and 0.12g of kiwi vine stem exudate polysaccharide (KVSEP) (mass ratio approximately 3.75:1), dissolve in 15L of deionized water, stir at 500rpm and 45℃ for 40min until fully dissolved, to obtain a whole biomass green suspension with strong viscous plasticity and pH that is naturally determined by the OPP / KVSEP ratio; no chemical dispersants or chemical pH adjusters are added throughout the process.
[0044] A4. Add 7.5g of modified carbon fiber filaments to the green suspension, pre-disperse by combing stirring for 5min, and then start ultrasonic dispersion. The carbon fiber is evenly dispersed by the steric hindrance and viscoplasticity of the OPP / KVSEP system itself, without the need to add any dispersant. Then add 42.5g of PA6 fiber (15wt% carbon fiber content) and wet mix for 10min, and filter.
[0045] A5. After filtering, the felt material is dried by hot air circulation at 130℃ for 6 hours to completely remove the water phase, thus obtaining carbon fiber / PA6 fiber felt material.
[0046] A6. Place the carbon fiber felt in a 200×150mm mold, place it on a flat vulcanizing machine, and hot-press it according to a two-stage pre-compression-molding process: ① Pre-compression stage—heat to 270℃ at 5℃ / min, maintain low pressure at 0.3MPa for 12min, so that the residual OPP / KVSEP polysaccharide is completely pyrolyzed into CO2 and H2O in a breathable state within this thermal decomposition temperature range, and is discharged and escaped through the pore channels of the fiber felt, the suspension is completely removed, and there is no residue, achieving minimal residue. ① No bubbles, low porosity; ② Molding stage - adjust the temperature to 250℃, pre-press at 0.5MPa to melt PA6 fibers and hold for 5 minutes, then increase the pressure to 3MPa and hold for 10 minutes to impregnate, and use the residual pore channels in the felt to release internal bubbles, achieving dense structure and high crystallinity; finally, gradient cooling and pressure holding, cooling at 3℃ / min to 180℃, 7℃ / min to 100℃, and 15℃ / min to room temperature, maintaining 3MPa pressure throughout, and demolding.
[0047] A7. The resulting board is annealed at 160℃ for 1 hour and then slowly cooled.
[0048] Example 3 (PPS matrix, 30mm carbon fiber, carbon fiber content 20wt%)
[0049] A1, carbon fiber filaments are desizing in a 500℃ high-temperature furnace for 1 hour.
[0050] A2. The desized carbon fiber was cut to 30mm, sized and modified in a 1wt% compatible PPS sizing agent aqueous dispersion for 5min, and then dried to obtain modified carbon fiber.
[0051] A3. Weigh 0.45g of okra pod polysaccharide (OPP) and 0.12g of kiwi vine stem exudate polysaccharide (KVSEP) (mass ratio approximately 3.75:1), dissolve in 15L of deionized water, stir at 500rpm and 45℃ for 40min until fully dissolved, to obtain a whole biomass green suspension with strong viscous plasticity and pH that is naturally determined by the OPP / KVSEP ratio; no chemical dispersants or chemical pH adjusters are added throughout the process.
[0052] A4. Add 10g of modified carbon fiber to the green suspension, pre-disperse by combing stirring for 5min, and then start ultrasonic dispersion. The carbon fiber is evenly dispersed by the steric hindrance and viscoplasticity of the OPP / KVSEP system itself, without the need to add a dispersant. Then add 40g of PPS fiber (20wt% carbon fiber content) and wet mix for 10min, and filter.
[0053] A5. After filtering, the felt material is dried by hot air circulation at 130℃ for 6 hours to completely remove the aqueous phase, thus obtaining carbon fiber / PPS fiber felt material.
[0054] A6. Place the carbon fiber felt in a 200×150mm mold, place it on a flat vulcanizing machine, and hot-press it according to a two-stage pre-compression molding process: ① Pre-compression molding stage—heat to 290℃ at 5℃ / min, maintain low pressure at 0.3MPa for 12min, so that the residual OPP / KVSEP polysaccharide is completely pyrolyzed into CO2 and H2O in a breathable state within this thermal decomposition temperature range, and is discharged and escaped through the pore channels of the fiber felt, the suspension is completely removed, and there is no residue, achieving minimal or no bubbles. ① Low porosity; ② Molding stage – Continue heating at 5℃ / min to 320℃, pre-press at 0.5MPa to melt PPS fibers and hold for 5min, then pressurize to 8MPa and hold for 20min, and utilize the residual pore channels in the felt to release internal air bubbles, achieving dense structure and high crystallinity; finally, gradient cooling and pressure holding, cooling at 3℃ / min to 250℃, 7℃ / min to 150℃, and 15℃ / min to room temperature, maintaining 6MPa pressure throughout, and demolding.
[0055] A7. The resulting sheet was annealed at 200℃ for 1 hour and then slowly cooled.
[0056] Example 4 (PEEK matrix, 80mm carbon fiber, carbon fiber content 30wt%)
[0057] A1, carbon fiber filaments are desizing in a 500℃ high-temperature furnace for 1 hour.
[0058] A2. The desized carbon fiber was cut to 80mm, sized and modified in a 1wt% ammoniated PEEK sizing agent aqueous dispersion for 5min, and then dried to obtain modified carbon fiber.
[0059] A3. Weigh 0.45g of okra pod polysaccharide (OPP) and 0.12g of kiwi vine stem exudate polysaccharide (KVSEP) (mass ratio approximately 3.75:1), dissolve in 15L of deionized water, stir at 500rpm and 45℃ for 40min until fully dissolved, to obtain a whole biomass green suspension with strong viscous plasticity and pH that is naturally determined by the OPP / KVSEP ratio; no chemical dispersants or chemical pH adjusters are added throughout the process.
[0060] A4. Add 15g of modified carbon fiber to the green suspension, pre-disperse by combing stirring for 5min, and then start ultrasonic dispersion. The carbon fiber is evenly dispersed by the steric hindrance and viscoplasticity of the OPP / KVSEP system itself, without the need to add any dispersant. Then add 35g of PEEK fiber (30wt% carbon fiber content, CF:PEEK=3:7) and wet mix for 10min, then filter.
[0061] A5. After filtering, the felt material is dried by hot air circulation at 130℃ for 6 hours to completely remove the aqueous phase, thus obtaining carbon fiber / PEEK fiber felt material.
[0062] A6. Place the carbon fiber felt in a 200×150mm mold, place it on a flat vulcanizing machine, and hot-press it according to a two-stage pre-compression molding process: ① Pre-compression molding stage—heat to 300℃ at 5℃ / min, maintain low pressure at 0.3MPa for 15min, so that the residual OPP / KVSEP polysaccharide is completely pyrolyzed into CO2 and H2O in a breathable state within this thermal decomposition temperature range, and is discharged and escaped through the pore channels of the fiber felt, the suspension is completely removed, and there is no residue, achieving low bubble and low temperature. Porosity; ② Molding stage - continue heating at 5℃ / min to 385℃, pre-press at 0.5MPa to melt PEEK fibers and hold for 5min, then pressurize to 18MPa and hold for 35min, and use the residual pore channels in the felt to release internal air bubbles, achieving dense structure and high crystallinity; finally, gradient cooling and pressure holding, cooling at 3℃ / min to 300℃, 7℃ / min to 200℃, and 15℃ / min to room temperature, maintaining 12MPa pressure throughout, and demolding.
[0063] A7. The resulting sheet was annealed at 250°C for 1 hour and then slowly cooled.
[0064] Comparative Example 1 (Carbomer suspension, same wet process, carbon fiber content 25wt%)
[0065] A1, carbon fiber filaments are desizing in a 500°C furnace for 1 hour (same as Example 1).
[0066] A2, the desized carbon fiber was cut to 50 mm, sized and modified in a 1 wt% ammoniated PEEK sizing agent aqueous dispersion for 5 min, and then dried to obtain modified carbon fiber (same as Example 1).
[0067] A3, Preparation of carbomer suspension: Weigh 30g of carbomer and add it to 15L of deionized water. After stirring and dissolving, add triethanolamine to adjust the pH to 8.0 to obtain a 0.2wt% carbomer suspension (containing the chemical dispersant carbomer and the chemical pH adjuster triethanolamine) to replace the OPP / KVSEP whole biomass green suspension; the suspension volume is the same as in Example 1.
[0068] A4. Add 12g of modified carbon fiber to the above carbomer suspension, pre-disperse by combing and stirring for 5min, then start ultrasonic dispersion; add 36g of PEEK fiber (carbon fiber content 25wt%, CF:PEEK=1:3) and wet mix for 10min, then filter.
[0069] A5. The filtered felt material was dried by hot air circulation at 130°C for 6 hours to obtain carbon fiber / PEEK fiber felt material (same as in Example 1).
[0070] A6. Place the carbon fiber felt in a 200×150mm mold, place it on a flat vulcanizing machine, and hot press it according to the same two-stage pre-compression-molding process as in Example 1: ① Pre-compression molding stage: heat up to 300℃ at 5℃ / min, maintain low pressure of 0.3MPa for 15min; ② Molding stage: continue to heat up to 380℃ at 5℃ / min, pre-compress at 0.5MPa to melt the PEEK fiber and maintain the temperature for 5min, then increase the pressure to 16MPa and hold for 30min; finally, gradually decrease the temperature and pressure, decreasing to 300℃ at 3℃ / min, decreasing to 200℃ at 7℃ / min, decreasing to room temperature at 15℃ / min, maintaining a pressure of 10MPa throughout, and then demold.
[0071] A7. The obtained board is annealed at 250°C for 1 hour and then slowly cooled (same as in Example 1).
[0072] Comparative Example 2 (Traditional continuous fiber prepreg laminated and hot-pressed, with interlayer separation)
[0073] A1. Cutting the prepreg. Cut the continuous carbon fiber / PEEK unidirectional prepreg into prepreg sheets according to the mold size (200×150mm).
[0074] A2, Quasi-isotropic layup. The cut prepreg is laid and stacked layer by layer in a quasi-isotropic manner (e.g., [0° / +45° / 90° / -45°]s) to make the fiber volume fraction the same as in Example 1, so as to obtain the prepreg laminate blank.
[0075] A3, Hot pressing. The laminated blank is placed in a 200×150mm mold and placed on a flat vulcanizing machine. Hot pressing is performed at the same temperature and pressure as in Example 1: the temperature is increased to 380℃ at 5℃ / min, pre-pressed at 0.5MPa and held for 5min, then the pressure is increased to 16MPa and held for 30min for impregnation; then the temperature is decreased to 300℃ at 3℃ / min, decreased to 200℃ at 7℃ / min, and decreased to room temperature at 15℃ / min, while maintaining a pressure of 10MPa throughout the process. After demolding, the laminated composite material sheet is obtained.
[0076] A4. The obtained board is annealed at 250°C for 1 hour and then slowly cooled (same as in Example 1).
[0077] Comparative Example 3 (PEG suspension + powdered resin, same wet process, carbon fiber content 25wt%)
[0078] A1, carbon fiber filaments are desizing in a 500°C furnace for 1 hour (same as Example 1).
[0079] A2, the desized carbon fiber was cut to 50 mm, sized and modified in a 1 wt% ammoniated PEEK sizing agent aqueous dispersion for 5 min, and then dried to obtain modified carbon fiber (same as Example 1).
[0080] A3, Preparation of PEG suspension: Weigh 30g of polyethylene glycol (PEG) and add it to 15L of deionized water, stir to dissolve, and obtain 0.2wt% PEG suspension to replace OPP / KVSEP whole biomass green suspension; the volume of suspension is the same as in Example 1.
[0081] A4. Add 12g of modified carbon fiber to the above PEG suspension, pre-disperse by combing and stirring for 5min, and then start ultrasonic dispersion; then add 36g of powdered PEEK (particle size D50≈25μm, the same mass as PEEK fiber in Example 1, carbon fiber content 25wt%) and wet mix for 10min, and filter.
[0082] A5. The filtered felt material was dried by hot air circulation at 130℃ for 6 hours to obtain carbon fiber / PEEK powder felt material.
[0083] A6. Place the carbon fiber felt in a 200×150mm mold, place it on a flat vulcanizing machine, and hot press it according to the same two-stage pre-compression-molding process as in Example 1: ① Pre-compression molding stage: heat up to 300℃ at 5℃ / min, maintain low pressure of 0.3MPa for 15min; ② Molding stage: continue to heat up to 380℃ at 5℃ / min, pre-compress at 0.5MPa to melt the powdered PEEK and maintain the temperature for 5min, then increase the pressure to 16MPa and hold for 30min; finally, gradually decrease the temperature and pressure, decreasing to 300℃ at 3℃ / min, decreasing to 200℃ at 7℃ / min, decreasing to room temperature at 15℃ / min, maintaining a pressure of 10MPa throughout, and then demold.
[0084] A7. The obtained board is annealed at 250°C for 1 hour and then slowly cooled (same as in Example 1).
[0085] Performance Comparison
[0086] Table 1 provides a reference for the performance test data of carbon fiber reinforced thermoplastic composite plates prepared by Examples 1-4 and Comparative Examples 1-3 (tensile strength according to GB / T 1040.2, flexural strength according to GB / T 9341, interlaminar shear strength ILSS according to GB / T3357 short beam shear method, porosity according to Archimedes density method, and mechanical properties are taken as the average of 5 parallel samples).
[0087] Table 1. Comparison of composite material properties between the examples and comparative examples
[0088] sample Tensile strength (MPa) Bending strength (MPa) Interlaminar shear strength (ILSS) (MPa) Porosity (%) Dispersant cost (RMB / kg) Example 1 (PEEK, 50mm, 25%) 445 745 265 0.3 3~12 Example 2 (PA6, 50mm, 15%) 300 520 230 0.4 3~12 Example 3 (PPS, 30mm, 20%) 325 575 238 0.4 3~12 Example 4 (PEEK, 80mm, 30%) 475 780 278 0.2 3~12 Comparative Example 1 (Carbomer, 25%) 260 475 210 1.8 80~200 Comparative Example 2 (Laminated Prepreg) 300 510 78 2.6 — Comparative Example 3 (PEG + powder, 25%) 160 285 106 3.6 Approximately 20
[0089] Test results show that: (1) Biomass dispersant is better - Compared with the comparative example 1 which uses carbomer, Example 1, which uses all-biomass green suspension (OPP / KVSEP), has a porosity that is reduced from 1.8% to 0.3% and an ILSS that is increased from 210MPa to 265MPa. It does not introduce any chemical reagents, costs less than 1 / 10 of carbomer, and is completely biodegradable. (2) Two-stage pre-compression molding has better performance and no residue - with the two-stage pre-compression molding process (the pre-compression molding stage is vented and exited, and the molding stage is pressurized and melted and infiltrated), the residual polysaccharides are completely pyrolyzed and released before densification, with no organic residue. Compared with Comparative Example 3 which uses PEG+ powder resin, the porosity of Example 1 decreased from 3.6% to 0.3%, and the ILSS increased from 106MPa to 265MPa. Although Comparative Example 3 is also a wet process, it uses powder resin instead of thermoplastic fiber. During felting and hot pressing, the resin migrates and is lost in the form of particles and fails to form a three-dimensional network skeleton with fiber interlocking with carbon fiber. The densification is insufficient and the porosity is high, so its ILSS is still low. Ultimately, this invention achieves excellent comprehensive performance with a tensile strength of 300-475 MPa, a flexural strength of 520-780 MPa, an ILSS of 230-278 MPa (far higher than the 78 MPa of the composite structure in Comparative Example 2), and a porosity of ≤0.5% with a carbon fiber content of only 15-30 wt%.
[0090] The above embodiments and comparative examples are provided to enable those skilled in the art to understand and use the present invention. It will be apparent to those skilled in the art that various modifications can be easily made to these embodiments, and the general principles described herein can be applied to other embodiments without inventive effort. Therefore, the present invention is not limited to the above embodiments and comparative examples, and any improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the protection scope of the present invention.
Claims
1. A method for preparing carbon fiber reinforced thermoplastic composite materials using an okra-kiwi vine stem green suspension method, characterized in that, Includes the following steps: (1) Short carbon fiber filaments are subjected to desizing and surface modification treatment to obtain modified carbon fiber, so as to improve the interfacial bonding performance between carbon fiber filaments and thermoplastic matrix. (2) Using okra pod polysaccharide and kiwi vine stem exudate polysaccharide in a mass ratio of 2:1 to 5:1 and dissolved in water to form a whole biomass green suspension as the dispersion medium, the total mass concentration of the suspension is 0.1 to 0.4 wt%; modified carbon fiber and thermoplastic fiber are added to the suspension in a weight ratio of 1:9 to 1:1 and wet-mixed evenly. A green biomass suspension composed solely of okra pod polysaccharide, kiwifruit vine stem exudate polysaccharide, and water was obtained. This suspension inhibits fiber sedimentation when left to stand and promotes uniform fiber dispersion under high shear or ultrasonic dispersion. The acidic carboxylic acid groups of the okra pod polysaccharide become negatively charged after ionization, forming electrostatic steric hindrance on the fiber and particle surfaces. The kiwifruit vine stem exudate polysaccharide forms a physical adsorption protective layer at the carbon fiber-water interface and on the thermoplastic fiber surface. The viscosity, viscoplastic rheological behavior, surface charge, and pH of the suspension are controlled by adjusting the concentration and mass ratio of the okra pod polysaccharide and the kiwifruit vine stem exudate polysaccharide. (3) Filter the mixture obtained in step (2) and dry it until the residual moisture is ≤0.08wt% to obtain carbon fiber / thermoplastic fiber felt. Filtering and drying remove the aqueous phase from the suspension. (4) The felt material described in step (3) is hot-pressed using a two-stage pre-pressing-molding process: First, in the pre-pressing stage, the temperature is raised to the thermal decomposition temperature range of okra pod polysaccharide and kiwi vine stem exudate polysaccharide under a pressure of 0.2~1MPa, that is, 245~315℃, and kept at this temperature for 10~20min. At this stage, the felt material has not yet become dense and remains loose and breathable, so that the okra pod polysaccharide and kiwi vine stem exudate polysaccharide remaining in the felt material are completely pyrolyzed into CO2 and H2O and discharged through the fiber felt pore channels; then, in the molding stage, the temperature is raised to above the melting or softening temperature of thermoplastic fibers and below the thermal decomposition temperature to melt them, and then the pressure is raised to 1~20MPa and kept at 10~40min to allow the melt of thermoplastic fibers to fully infiltrate carbon fibers and solidify them, and the internal air bubbles are released by using the residual pore channels in the felt material. Finally, the temperature is gradually reduced and the pressure is kept low before demolding to obtain carbon fiber reinforced thermoplastic composite material board.
2. The method for preparing carbon fiber reinforced thermoplastic composite material using the okra-kiwi vine stem green suspension method according to claim 1, characterized in that, The surface modification treatment of carbon fiber in step (1) includes one of the following: sizing coating, surface oxidation, chemical grafting, plasma treatment, or a combination of different modification methods; the sizing coating uses a thermoplastic sizing agent that is homologous to or compatible with the selected thermoplastic matrix and resistant to the corresponding processing temperature, the concentration of the sizing agent is 0.5~2wt%, and the treatment time is 2~10min.
3. The method for preparing carbon fiber reinforced thermoplastic composite material using the okra-kiwi vine stem green suspension method according to claim 1, characterized in that, The carbon fiber mentioned in step (1) is short-cut carbon fiber with a length of 30~100mm, a single filament diameter of 5~10μm, a tensile strength ≥3000MPa, and an elastic modulus ≥230GPa.
4. The method for preparing carbon fiber reinforced thermoplastic composite material using the okra-kiwi vine stem green suspension method according to claim 1, characterized in that, The viscosity, viscoplastic rheological behavior, surface charge and pH of the whole biomass green suspension described in step (2) are controlled by adjusting the concentration and mass ratio of okra pod polysaccharide and kiwi vine stem exudate polysaccharide. When the proportion of okra pod polysaccharide increases, the carboxylate density of the system increases, the negative charge is enhanced, the electrostatic steric hindrance effect is enhanced, and the pH tends to be acidic. When the proportion of kiwi vine stem exudate polysaccharide increases, the amphiphilic steric hindrance protection is enhanced and the pH tends to be neutral.
5. The method for preparing carbon fiber reinforced thermoplastic composite material using the okra-kiwi vine stem green suspension method according to claim 1, characterized in that, The okra pod polysaccharide is derived from okra food processing waste pods and is an acidic polysaccharide composed of galacturonic acid, rhamnose, galactose and arabinose, with a weight-average molecular weight (Mw) of 80-300 kDa. The kiwifruit vine stem exudate polysaccharide is derived from the exudate from the cut ends of kiwifruit pruning waste vine stems and is an arabinogalactan with galactose as the backbone, with a weight-average molecular weight (Mw) of 150-600 kDa.
6. The method for preparing carbon fiber reinforced thermoplastic composite material using the okra-kiwi vine stem green suspension method according to claim 1, characterized in that, When okra pod polysaccharide and kiwi vine stem exudate polysaccharide are mixed in a mass ratio of 3:1 to 4:1 to form a suspension, the thixotropic index (TI) is 3.5 to 7.
0.
7. The method for preparing carbon fiber reinforced thermoplastic composite material using the okra-kiwi vine stem green suspension method according to claim 1, characterized in that, The thermoplastic fiber mentioned in step (2) is a thermoplastic staple fiber made by cutting continuous filaments obtained by melt spinning of thermoplastic resin. The diameter of the single filament is 10~50μm and the length is 50~100mm. The thermoplastic resin is one or a combination of two or more of polyether ether ketone, polyamide, polyphenylene sulfide, polyetherimide and polypropylene. The thermoplastic fiber is intertwined and overlapped with carbon fiber filaments in the suspension to form a three-dimensional network skeleton of interlocking fibers.
8. The method for preparing carbon fiber reinforced thermoplastic composite material using the okra-kiwi vine stem green suspension method according to claim 1, characterized in that, In step (4), the hot pressing parameters for different thermoplastic matrices are as follows: for polyetheretherketone (PEEK) matrix, the hot pressing temperature is 360~400℃ and the pressure is 5~20MPa; for polyamide or polypropylene matrix, the hot pressing temperature is 180~300℃ and the pressure is 1~5MPa; for polyetherimide or polyphenylene sulfide (PPS) matrix, the hot pressing temperature is adjusted accordingly between PEEK and PEM. For semi-crystalline thermoplastic resins such as PEEK, PEM, and PPS, further heat treatment is performed after hot pressing to regulate the crystallinity of the matrix and eliminate internal stress.
9. The method for preparing carbon fiber reinforced thermoplastic composite material using the okra-kiwi vine stem green suspension method according to claim 1, characterized in that, The hot pressing process described in step (4) uses a flat vulcanizing machine as the hot pressing device.
10. The okra-kiwi vine stem green suspension carbon fiber reinforced thermoplastic composite material prepared by the method according to any one of claims 1 to 9, characterized in that, The carbon fiber reinforced thermoplastic composite material sheet is an integral homogeneous structure formed by the three-dimensional random entanglement of carbon fiber and thermoplastic fiber, without resin-rich interlayer weak surfaces.
